Psychological dynamics and swimmers’ performance: a literature review - Turinah; Tomoliyus; Sukamti, Endang Rini; Alim, Abdul (Indonesian Journal of Sport Management, 2025)
Background: Swimmer performance is not solely determined by physical ability and technical skills but is significantly influenced by psychological dynamics such as mental fatigue, anxiety, self-confidence, stress, motivation, and psychological recovery. Purpose: This literature review aims to examine and synthesize recent quantitative studies (2021–2025) that investigate the influence of psychological factors on swimming performance. Methods: The PRISMA method was used to select 11 studies from a total of 120 academic articles obtained through Google Scholar, PubMed, and Frontiers in Sports and Active Living. Exclusion criteria included conference proceedings, qualitative studies, books, and other literature reviews. Results: Findings reveal that mental fatigue and pre-competition anxiety negatively affect athletes’ performance, impacting sleep quality, hormonal balance, and emotional readiness. In contrast, psychological recovery strategies, high motivation, and self-confidence contribute to improved performance, mood, and technical execution. Stress, caused by both internal expectations and external pressure, exacerbates fatigue and reduces focus. Conclusion: These psychological aspects are interrelated and play a crucial role in competitive swimming performance. Psychological skills such as self-talk, visualization, tapering strategies, and emotional regulation are essential for managing mental stressors. Implications and Recommendation: Integrating psychological training into conventional coaching programs is necessary to maintain both physical and mental balance in athletes. Coaches and sports psychologists are advised to conduct regular monitoring of athletes’ psychological conditions and implement appropriate psychological interventions. Future research should employ longitudinal and multidimensional designs to better understand the relationship between psychological resilience and athletic achievement.